Exploring of paritaprevir and glecaprevir resistance due to A156T mutation of HCV NS3/4A protease: molecular dynamics simulation study. Issue 12 (14th July 2022) - Boonma, Thitiya; Nutho, Bodee; Darai, Nitchakan; Rungrotmongkol, Thanyada; Nunthaboot, Nadtanet
Abstract: Hepatitis C virus (HCV) NS3/4A serine protease is a promising drug target for the discovery of anti-HCV drugs. However, its amino acid mutations, particularly A156T, commonly lead to rapid emergence of drug resistance. Paritaprevir and glecaprevir, the newly FDA-approved HCV drugs, exhibit distinct resistance profiles against the A156T mutation of HCV NS3/4A serine protease. To illustrate their different molecular resistance mechanisms, molecular dynamics simulations and binding free energy calculations were carried out on the two compounds complexed with both wild-type (WT) and A156T variants of HCV NS3/4A protease. QM/MM-GBSA-based binding free energy calculations revealed that the binding affinities of paritaprevir and glecaprevir towards A156T NS3/4A were significantly reduced by ∼4 kcal/mol with respect to their WT complexes, which were in line with the experimental resistance folds. Moreover, the relatively weak intermolecular interactions with amino acids such as H57, R155, and T156 of NS3 protein, the steric effect and the destabilized protein binding surface, which is caused by the loss of salt bridge between R123 and D168, are the main contributions for the higher fold-loss in potency of glecaprevir due to A156T mutation. An insight into the difference of molecular mechanism of drug resistance against the A156T substitution among the two classes of serine protease inhibitors could be useful for further optimization of new generation HCV NS3/4A inhibitors with enhanced inhibitory potency. Communicated by Ramaswamy H. Sarma